2006
DOI: 10.1002/app.25253
|View full text |Cite
|
Sign up to set email alerts
|

Barrier properties of polypropylene/organoclay nanocomposites

Abstract: Polypropylene/clay nanocomposites are attractive candidates for applications requiring good barrier properties because of the inherent features of the polymer matrix. To assess their potential, systematic research relating the barrier performance to the structural characteristics of polypropylene/montmorillonite samples has been conducted. The nanocomposites have been tested in the presence of helium, water vapor, toluene, and methanol, and the unmodified matrix has been found to exhibit better properties than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 16 publications
2
35
0
2
Order By: Relevance
“…Nanocompósitos compatibilizados com EVOH (P415OHAPO) apresentam morfologia intercalada ordenada caracterizada pelo perfil do plano difratado (001) da argila, bem definido cuja abertura corresponde a 3,65 nm. Por outro lado, quando os nanocompósitos foram compatibilizados com PP-g-AM (P415AMAPO), a distância interplanar basal da argila (001) foi superior a 3,65 nm e uma banda é observada sugerindo que neste caso nanocompósitos com estrutura intercalada desordenada foram obtidos devido a maior penetração das cadeias poliméricas entre as camadas da argila [15,17,38] . Embora nanocompósitos tenham sido obtidos quando os sistemas PP/argila organofílica APO foram compatibilizados com EVOH e PP-g-AM, o último mostrou um melhor efeito compatibilizante devido à maior abertura do plano basal (intercalação) juntamente com a quebra parcial da estrutura cristalina (esfoliação parcial) da argila.…”
Section: Resultsunclassified
“…Nanocompósitos compatibilizados com EVOH (P415OHAPO) apresentam morfologia intercalada ordenada caracterizada pelo perfil do plano difratado (001) da argila, bem definido cuja abertura corresponde a 3,65 nm. Por outro lado, quando os nanocompósitos foram compatibilizados com PP-g-AM (P415AMAPO), a distância interplanar basal da argila (001) foi superior a 3,65 nm e uma banda é observada sugerindo que neste caso nanocompósitos com estrutura intercalada desordenada foram obtidos devido a maior penetração das cadeias poliméricas entre as camadas da argila [15,17,38] . Embora nanocompósitos tenham sido obtidos quando os sistemas PP/argila organofílica APO foram compatibilizados com EVOH e PP-g-AM, o último mostrou um melhor efeito compatibilizante devido à maior abertura do plano basal (intercalação) juntamente com a quebra parcial da estrutura cristalina (esfoliação parcial) da argila.…”
Section: Resultsunclassified
“…Thus, even though the individual MA group interactions with the silicate are weaker than the corresponding ammonium cation interactions with the silicate layers, 28 the MA-treated PP can promote the formation of a filler network structure -and consequently result in a solid-like rheological response-because of their ability to effectively bridge silicate sheets. Similar filler networks, and the same qualitative rheological trend, have also been observed in montmorillonite filled nanocomposites of polyolefin random copolymers, 8 namely polyethylene-randomvinyl acetate (EVA); however, for these EVA systems, a much higher polar comonomer fraction is necessary (28 wt % of VA was used in that study 8 ) to achieve a comparable solidlike response with the one observed here.…”
Section: Thermal Characterizationmentioning
confidence: 99%
“…Through the incorporation of nano-sized particles into a pure polymer matrix, and through proper dispersion and orientation of these particles, significant reduction of the gas permeability can be achieved [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. These fillers create a tortuous path or maze which restricts the migration of the diffusing gas molecules through the polymer matrix by increasing the path length.…”
Section: Introductionmentioning
confidence: 99%